2018
DOI: 10.1556/2006.7.2018.106
|View full text |Cite
|
Sign up to set email alerts
|

The effect of loss-limit reminders on gambling behavior: A real-world study of Norwegian gamblers

Abstract: BackgroundOver the past two decades, problem gambling has become a public health issue and research from many countries indicates that a small but significant minority of individuals are problem gamblers. In Norway, the prevalence of problem gambling among adults is estimated to be just less than 1%. To help minimize the harm from gambling, the Norwegian government’s gambling operator (Norsk Tipping) has introduced several responsible gambling initiatives to help protect players from developing gambling proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 49 publications
2
31
1
Order By: Relevance
“…However, players who set voluntary limits without being prompted to do so lost more money gambling than players who did not set limits. Auer et al (2018b) found that information that reminds players that they had just spend 80% of their personal-set limit decreased monetary gambling intensity in consecutive months. Among video lottery players in Nova Scotia, a Canadian study by Focal Research (2007) found that RG features (including limit-setting tools) generally reduced the overall levels of gambling expenditure.…”
Section: Online Gambling Limit-setting and Behavioural Trackingmentioning
confidence: 99%
“…However, players who set voluntary limits without being prompted to do so lost more money gambling than players who did not set limits. Auer et al (2018b) found that information that reminds players that they had just spend 80% of their personal-set limit decreased monetary gambling intensity in consecutive months. Among video lottery players in Nova Scotia, a Canadian study by Focal Research (2007) found that RG features (including limit-setting tools) generally reduced the overall levels of gambling expenditure.…”
Section: Online Gambling Limit-setting and Behavioural Trackingmentioning
confidence: 99%
“…6 Consequently, many socially responsible gambling operators now offer their clientele a variety of responsible gambling tools 7 to help players keep in control of the amount of time and money they spend online, and include tools such as limit-setting (allowing gamblers to predetermine the amount of time and/or money they want to spend in a given time period [day/week/month]), self-exclusions (allowing gamblers to exclude themselves from gambling on the website for predetermined amounts of time), pop-up messaging (providing in-play information as to how much time and/or money gamblers have spent in session), and personalized messaging (providing information to gamblers about various aspects of their gambling behavior and/or recommendations about what they can do to stay in control). 7,8 One of the most popular types of responsible gambling tools is limit-setting. 7,8 A recent study carried out among 50 of the world's most popular online gambling sites found that the majority of them (90 percent) offered players voluntary limit-setting tools.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 One of the most popular types of responsible gambling tools is limit-setting. 7,8 A recent study carried out among 50 of the world's most popular online gambling sites found that the majority of them (90 percent) offered players voluntary limit-setting tools. 9 Despite the widespread use of limitsetting tools among popular gambling websites, very little research has examined their effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 The Norwegian government helped gamblers control their impulsivity using limit-setting tools, voluntary self-exclusion, and personalized feedback. 22 The internal consistency (Cronbach' s α=0.89) and test-retest reliability of the WBGS (r=0.77, p<0.001) were relatively good and were accepted as reasonable. The criterion-related validity comparing the high-risk group and low-risk group was also statistically significant.…”
Section: Discussionmentioning
confidence: 99%